Analysis on the development of environmental disclosure practices by selected Malaysian companies from 1999 to 2002 / Haslinda Yusoff, Normahiran Yatim and Noraini Mohd Nasir - Yusoff, Haslinda; Yatim, Normahiran; Mohd Nasir, Noraini (Accounting Research Institute (ARI) & Faculty of Accountancy, 2005)
Issues on environmental accounting and reporting have grasped the attention of accounting researchers since the 1970s. Continuous researches indicate the significance of integrating environmental matters in accounting. However, these initiatives have yet to develop a harmonization acceptance on the voluntary exercise. This is evidenced by the mixed global practices, with countries such as Netherlands having made environmental reporting mandatory, while the US encourage the practices. And in many other parts of the world, including Malaysia, environmental reporting is still a voluntary exercise. This study looks at the trend of environmental information disclosed in the corporate annual reports by selected Malaysian companies for the year 1999 to 2002. The findings revealed that majority of the companies are improving their environmental disclosure practices from a non-disclosure to a more qualitative disclosure state. They even started to quantitatively disclose certain environmental items such as environmental management and product ecology information. The development also results many companies disclosing their environmental concerns in a separate section in their annual report.